KHIND: rice cooker / Muhammad Aiman Azhar - Azhar, Muhammad Aiman (2022)
This subject is an attempt to teach students how to understand and study the business theory of a specific company so that it can be applied in a practical situation. As a result, I was given the opportunity to study the business theory and rules that govern the operation of a product manufactured by KHIND Holdings Berhad (KHIND), a Malaysian company. In the first section, I must research the purpose of this case study as well as the problem statement encountered by this company. In the following section, I assigned a task to research their company's background, select a product from their company, and figure out how the product works in terms of technology components. In addition, I gather information on how KHIND deals with and manages their business strategy in order to achieve their business goals and perform effective management. The majority of the information was gathered from their company's website, as well as a few secondary sources to back up all of the facts. In this case study, I used SWOT analysis to assess this company's strengths, weaknesses, opportunities, and threats in real-world business. As a result, in the final section, I was asked to come up with a few solutions to overcome or improve consumer need and demand.